Some Curvature Properties in LP-Sasakian Manifolds with Respect to Generalized Tanaka Webster Okumura Connection - Akbar, Ali; Sarkar, A; Ali, Md Showkat (GANIT: Journal of Bangladesh Mathematical Society, 2016)
The object of the present paper is to study LP-Sasakian manifolds with respect to generalized Tanaka Webster Okumura connection. We have studied locally ?-symmetric as well as locally projectively ?-symmetric LP-Sasakian manifolds with respect to a generalized Tanaka Webster Okumura connection. Locally ?-recurrent LP-Sasakian manifolds have also been studied with respect to generalized Tanaka Webster Okumura connection. GANIT J. Bangladesh Math. Soc.Vol. 34 (2014) 47-55